Surgical treatment experience of seven cases of Berry syndrome - Zhangke Guo; Zhimin Li; Feng Tong; Song Bai; Xiaofeng Li (Journal of Cardiothoracic Surgery)
Abstract Objective Berry syndrome is a group of rare congenital cardiac malformations including aortopulmonary window (APW), aortic origin of the right pulmonary artery (AORPA), interruption of the aortic arch (IAA), patent ductus arteriosus (PDA) (supplying the descending aorta) and intact ventricular septum. This paper will analyze the clinical data of 7 patients with Berry syndrome who underwent surgical treatment in our institution and discuss the one-stage surgical correction of Berry syndrome in combination with the literature. Methods From January 2013 to July 2024, a total of 7 children with Berry syndrome were admitted to the Cardiac Surgery Department of Beijing Children’s Hospital. The median age was 3 months (range, 1–36 months). All patients’ IAA morphology were type A. The APW morphology was type IIA in 2, type IIB in 4, and type III in 1 patient. Three different surgical correction techniques were used to repair the APW and AORPA, including intra-aortic patch in 2, RPA angioplasty with aortic cuff in 2, RPA detachment and reimplant in 3 patients. Results Among the 7 patients, one died in the early postoperative period, (1/7, 14.3%). The remaining 6 surviving patients, mechanical ventilation was lasted for 51 to 166 h postoperatively, with an average of (113.3 ± 50.8) hours; the CCU stay was 6 to 23 days, with an average of (11.8 ± 6.5) days. Two cases (2/7, 28.6%) of patients adopted the strategy of delayed sternal closure. The 6 surviving children were followed up for a period ranging from 3 to 132 months, with a median follow-up duration of 36 months. During the follow-up, 2 patients underwent a second operations (2/6, 33.3%). The remaining 4 patients showed no obvious RPA stenosis, descending aorta (DAO) stenosis, aortic valve stenosis or aortic valve regurgitation (AR) during the follow-up period. In the latest follow-up, the average velocity of the RPA of the 4 patients was 1.68 ± 0.36 m/s, and the average pressure gradient was 11.9 ± 4.8 mmHg; the average velocity of the DAO was 2.1 ± 1.7 m/s, and the average pressure gradient was 17.9 ± 2.6 mmHg. All the AR were less than mild. Conclusion Most children can achieve one-stage surgical correction. For children with APW type IIA, the intra-aortic patch method can be attempted, but its therapeutic effect still requires medium to long-term follow-up. The surgical approach of RPA detachment and reimplant can be applied to all types of patients with Berry syndrome, and the medium to long-term follow-up result is favorable. For the treatment of IAA, it is recommended that end-to-side anastomosis be performed between the DAO and the aortic arch, and the anterior wall be augmented by using bovine pericardial tissue patches. For the residual obstruction at the postoperative anastomosis site, balloon dilation angioplasty can be considered. Compression of the left main bronchus can be supported by intratracheal stents. Perspective Statement In the English literature accessed thus far, there are less than 50 cases associated with the surgical treatment of Berry syndrome. In this work, we analyzed the clinical data of 7 patients from January 2013 to July 2024 with Berry syndrome who underwent surgical treatment in our institution and showed one-stage surgical correction can achieved acceptable outcomes. Graphical Abstract